Penerapan Model Active Learning Tipe Kontrak Belajar disertai Kuis di Akhir Pembelajaran pada Siswa Kelas X. IPK 3 MAN 2 Pesisir Selatan sebagai Upaya untuk Meningkatkan Aktifitas dan Hasil Belajar pada Mata Pelajaran PKN - Desmayenti Desmayenti (Journal on Education, 2023)
This research was motivated by the low learning outcomes of class X students. GPA 3 for the 2022 academic year in PKN learning. This is because researchers still apply conventional methods in learning. The aim of the research is to describe and explain the process of increasing student learning activities and outcomes through the implementation of learning using the Active Learning method of learning contract types. The action hypothesis in this study is that the implementation of the Active Learning method of the learning contract type can increase the activities and learning outcomes of class X.GPA 3 Madrasah Aliyah Negeri (MAN) 2 Pesisir Selatan in the 2022 academic year in PKN subjects. The subjects in this study were students of class X. GPA 3 Madrasah Aliyah Negeri (MAN) 2 Pesisir Selatan for the 2022 academic year, totaling 35 people with different social and economic backgrounds. With these differences the teacher must be able to find the right method in learning. This research consists of two cycles. Cycle I consisted of four meetings. The first, second and third meetings focused on students' ability to understand the subject matter in groups, then ended with giving tests at the fourth meeting. In the implementation of cycle I, there were still many students who did not understand the material well. Therefore it is continued with the implementation of cycle II. The results showed that there had been changes in student learning outcomes. Completeness in the first cycle was 27 people with an average of 79.7, and in the second cycle there were 34 people with an average of 89.8. Student learning activities also show a significant increase in each indicator.